(3GdMSjfjI aj GdBOGHs - (3GdCfWGcj, MSjf Hf YHO Gddg, J (B1130 (3g`s ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; dc GdMeO dc GdTcQ dc Gdedc aJYWjg hdG jefY YWGAc dc GdMce hdG eYGQV dg dc GdEfTGA hdG efGbV dg EPG bdJe cdGeG fGbdG ajg s
(3BNQgG (B:s
(3hONd bHd age hGdJYQV deG dG ONd aj GdebUhO CYQV hCdaGX ZQjHI daX eLed hYO GdNUhe VYjaG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 617s
(3gOjI GdYGQajf (B1/ 325s
(3EjVGM Gdecfhf (B1/ 406s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs